Well-posedness of non-autonomous semilinear systems. Issue 16 (2019) - Schmid, Jochen; Dashkovskiy, Sergey; Jacob, Birgit; Laasri, Hafida
Abstract: We present well-posedness - along with global stability - results for non-autonomous semilinear input-output systems, the central assumption being that the considered system is scattering-passive. We consider both systems with distributed control and observation and systems with boundary control and observation.